Conversion from farmland to orchard or agroforestry improves soil carbon sequestration by enhancing microbial biological activity in Northwest China - Weixia Wang; Daniel F. Petticord; Shanchao Zhao; Guang Yang; Yuwen Chen; Xuansheng Huang (PLoS ONE, 2026)
Land-use conversion from conventional farmland to orchard or agroforestry systems holds great potential for enhancing soil organic carbon (SOC) sequestration and microbial activity in arid regions. This study investigated the impacts of such transitions in Northwest China, utilizing a 15-year chronosequence across seven land-use patterns. Soil profiles (0–30 cm) were analyzed for SOC, nutrient availability, and microbial biomass carbon (MBC) and nitrogen (MBN). Results demonstrated that the 15-year-old jujube-wheat alley cropping system (15JW) achieved the highest accumulation of SOC, MBC, and MBN, particularly in the topsoil (0–10 cm). Structural equation modeling (SEM) further elucidated the mechanisms driving microbial dynamics, revealing that substrate quality and phosphorus availability were the predominant controls. Specifically, the model explained 47.4% of the variation in MBC (R 2 = 0.474), with SOC exerting a significant direct influence (β = −0.35). In contrast, available phosphorus (AP) was identified as the primary driver of MBN (β = 0.52), contributing to 56.1% of its total variance (R 2 = 0.561). These findings suggest that long-term agroforestry management mitigates carbon loss by fostering stable nutrient-mediated microbial pools. Our research underscores that transitioning to mature agroforestry systems is a strategic measure for improving soil fertility and climate resilience in semi-arid ecosystems.